Colloidal Silica/Poly(Methacrylsiloxane) Nanocomposite Particles: Synthesis, Characterization, and Application in Toners. Issue 1663 (20th February 2014) - Fomitchev, Dmitry; Lewis, Russell; Tu, Hairuo; Cheng, Li; Kambara, Hajime; Moeser, Geoffrey
ABSTRACT: We report on a new class of materials for laser printer toner applications. These materials were prepared from methacrysilane-in-water emulsions stabilized with colloidal silica particles. In this elegant system, the colloidal silica particles reside at the water/oil interface helping to emulsify the oil droplet, self-organizing into a raspberry-like morphology. The emulsion formation is followed by free-radical polymerization, hydrophobic treatment, and drying steps. This one pot synthesis in water affords a hydrophobic material with a particle size in the range of 80 to 300 nm. The particle size could be fine-tuned by changing the oil-to-silica mass ratio or by using colloidal silica particles of different sizes. Results of material characterization by solid-state NMR, electron microscopy, and particle size measurements methods will be presented. Examples of possible extensions of the synthesis towards materials with methacrylsilane partially substituted with other methacrylates will be provided. Application of the new material in toners will be described as will the comparison of its performance with the incumbent material - hydrophobic colloidal silica.